United States. Post Office Dept. records - United States. Post Office Department; United States. General Post Office
Handwritten transcript of a letterbook of (1789 November 28-1805 March 15) containing copies of letters by postmasters general Gideon Granger, Joseph Habersham, Samuel Osgood, and Timothy Pickering; chart (1807) made by Gideon Granger; accounts (1804-1805, 1807) for the post office at Hamilton, Ohio; record book (1899 April 11-1906 September 25) of the post office at Cavetown, Md.; and essay (1912) entitled, Annals of the Post Office Department, 1607-1775, by E.F. Brown.
United States Office of the Postmaster General created by Continental Congress, July 26, 1775; United States General Post Office created by Congress, September 22, 1789, under the direction of the Postmaster General; United States Post Office Department created as government agency by Congress, February 20, 1792; reorganized as United States Postal Service in 1970.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brown, E. F; Granger, Gideon, -- 1767-1822 -- Correspondence; Habersham, Joseph, -- 1751-1815 -- Correspondence; Osgood, Samuel, -- 1748-1813 -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Cavetown Post Office (Cavetown, Md.); Hamilton Post Office (Hamilton, Ohio); United States. -- Postmaster General; Postal service -- Maryland -- Cavetown; Postal service -- Ohio -- Hamilton; Postal service -- United States -- History